Superheavyweight clean and jerk movement biomechanics: elementary analysis - Lovchev, A. V.; Kobyakov, Yu. P.; Bolotov, A. V. (Theory and Practice of Physical Culture, 2019)
The study analyzes the superheavyweight clean and jerk movement biomechanics versus the body length of the world record holders for the period of 1960-2015, with the movement sequence grouped into 8 elementary moves (motor units). The analysis was intended to check the assumption that the weight lifting movement biomechanics may be correlated with the body length. We applied a match correlation method to find a positive correlation between the movement sequence elements and body lengths - albeit the correlations were found widely varying and falling in conflict with the null hypothesis. It was further found that the clean height and squat depth are determined by the movement sequence elements rather than the body length alone. The data analysis completed on a systemic and logical basis found the correlations of the motor elements being determined by the length of the lower limb elements (shin and thigh) and their joint flexibility rates. The study data arrays and analyses give the reasons to conclude that these elements altogether largely determine the individual clean technique critical for success of the clean and jerk sequence.